Pengaruh Komunikasi, Perilaku Inovatif dan Knowledge Management Terhadap Kinerja Karyawan Astra Credit Companies Malang - Febriani, Rezki Febi; Mardani, Ronny Malavia; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted at Astra Credit Companies Malang located at Jalan Jaksa Agung Suprapto No. 28, Rampal Celaket, Klojen District, Malang City, East Java. This study aims to determine the influence of communication, innovative behavior and knowledge management on employee performance. The type of research used is quantitative research with a descriptive approach. The population in this study was employees of Astra Credit Companies Malang which amounted to 40 employees, then the total number of samples was taken using the saturated sampling method. Based on the results of the t-test data analysis showed that the significance value of communication variables and innovative behavior had an effect on employee performance, while knowledge management had no significant effect on employee performance. The results of the determination test showed that dependent variables can be predicted with 83% explaining independent factors such as communication, innovative behavior and knowledge management. In addition, the study uses a collection technique that formulates research data from closed questionnaires using google forms. Keywords: Comunication, Innovative Behavior and Knowledge Management